Association between activities related to routes of infection and clinical manifestations of melioidosis. (January 2016) - Lim, C.; Peacock, S.J.; Limmathurotsakul, D.
Abstract: We sought associations between route of infection by Burkholderia pseudomallei and clinical manifestations in 330 cases of melioidosis in northeast Thailand using bivariate multivariable logistic regression models. Activities related to skin inoculation were negatively associated with bacteraemia, activities related to ingestion were associated with bacteraemia, and activities related to inhalation were associated with pneumonia. Our study suggests that route of infection is one of the factors related to clinical manifestations of melioidosis.